Geochemical speciation of iron under nearshore hypoxia: A case study of Alappuzha mud banks, southwest coast of India. (1st April 2022) - Mathew, D.; Gireeshkumar, T.R.; Udayakrishnan, P.B.; Shameem, K.; Nayana, P.M.; Deepulal, P.M.; Sarath, R.; Nair, M.; Jaleel, A.K.U.; Balachandran, K.K.
Abstract: Studies on the speciation of iron (Fe) and its regulatory roles in the biogeochemical cycling of other elements in the sediments of the Arabian Sea are limited. Changes in the reactivity and crystallinity of geochemical forms of Fe were determined in the Alappuzha mud bank on the southwest coast of India, which experiences hypoxia during the southwest monsoon. Fortnightly time-series measurements were conducted from April to August 2016. Coastal upwelling was evident from June onwards and caused hypoxic water's incursion until August. The mud bank sediments are geochemically unique due to high concentrations of Fe, phosphorus (P) and moderate levels of organic matter, nitrogen (N), and sulfur (S). Geochemical speciation of Fe showed significant concentrations of easily reducible Fe oxides (FeOx1 ), reducible crystalline Fe oxides (FeOx2 ), sheet silicate bound Fe (FePRS ), unreactive Fe (FeU ), magnetite (FeMag ), and pyrite-bound Fe (FePyr ). The concentrations of total Fe (FeT ) and highly reactive Fe (FeHR ) in mud bank sediments were 63.5 and 37 mg/g, respectively, much higher than those in other coastal sediments, including upwelling zones. FeT remained in the sediments even under hypoxia, in contrast to the pronounced Mn decrease, indicating Mn mobilization from surface sediments. Various Fe ratios/indices such as FePyr /FeHR, and FeHR /FeT revealed anoxic and ferruginous conditions in the sediments during upwelling. Highly reactive Fe(III) oxides (FeOx1 and FeOx2 ) were the primary Fe pool in the mud bank sediments, and they effectively immobilized the free sulfide formed by sulfate reduction. The high sulfide buffering capacity is significant for the environment as it can rapidly immobilize the dissolved sulfide, a potent toxin for benthic and demersal organisms. Highlights: Sedimentary Fe speciation from a seasonally hypoxic coastal environment (mud banks). Easily reducible and reducible crystalline Fe oxides, as well as silicate bound Fe were the dominant forms in mud bank. Fe dynamics revealed anoxic, and ferruginous conditions in the mud bank. The abundance of P and Fe point towards the formation of Fe–P minerals (vivianite). Highly reactive Fe forms effectively immobilize the free sulfide in sediments.